2001
DOI: 10.1139/g01-058
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content and base composition in 28 taxa of Musa

Abstract: The nuclear DNA content of 28 taxa of Musa was assessed by flow cytometry, using line PxPC6 of Petunia hybrida as an internal standard. The 2C DNA value of Musa balbisiana (BB genome) was 1.16 pg, whereas Musa acuminata (AA genome) had an average 2C DNA value of 1.27 pg, with a difference of 11% between its subspecies. The two haploid (IC) genomes, A and B, comprising most of the edible bananas, are therefore of similar size, 0.63 pg (610 million bp) and 0.58 pg (560 million bp), respectively. The genome of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
2
14
0
3
Order By: Relevance
“…The diversity in genome size and genomic distribution of 5S loci observed within M. acuminata is on line with the previous studies on rDNA distribution (Doleželová et al, 1998;Osuji et al, 1998;Valá rik et al, 2002), genome size (Doležel et al, 1994;Lysá k et al, 1999;Kamaté et al, 2001) and variation at DNA level (Ude et al, 2002a). Hybridization between subspecies differing in the number of 5S rDNA sites could explain the origin of clonally propagated and seed sterile diploid clones with odd numbers of 5S rDNA sites observed previously (Doleželová et al, 1998;Osuji et al, 1998) and in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The diversity in genome size and genomic distribution of 5S loci observed within M. acuminata is on line with the previous studies on rDNA distribution (Doleželová et al, 1998;Osuji et al, 1998;Valá rik et al, 2002), genome size (Doležel et al, 1994;Lysá k et al, 1999;Kamaté et al, 2001) and variation at DNA level (Ude et al, 2002a). Hybridization between subspecies differing in the number of 5S rDNA sites could explain the origin of clonally propagated and seed sterile diploid clones with odd numbers of 5S rDNA sites observed previously (Doleželová et al, 1998;Osuji et al, 1998) and in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Until now, genome size has been determined for about 3,500 angiosperm species (Hanson et al, 2003). To our knowledge, nuclear DNA content was estimated in only six species of Musa (Doležel et al, 1994;Lysá k et al, 1999;D'Hont et al, 1999;Asif et al, 2001;Kamaté et al, 2001). All studies were performed using flow cytometry, which has been shown to be a rapid and reliable method for nuclear DNA content determination in plants (Doležel, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…acuminata and clones with AA genome is approximately 12 % larger than the B genome of M . balbisiana , with small intraspecific variation in nuclear DNA found in a number of wild M. acuminata diploid and parthenocarpic bananas and large variation exhibited among triploid cultivars (Kamaté et al ., ). Although intraspecific genetic diversity is an important attribute deemed critical for additive and dominance effects (Tilman et al ., ), there is limited understanding of the impact on population performance (Moore et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry (FCM) protocols have been applied for studying the natural variation in Musa nuclear genome size (DNA content) for taxonomic purposes and for checking ploidy among gene bank accessions and breeding materials [98][99][100][101]. The literature data suggest that, on average, the A genome of M. acuminata and clones with AA genome constitution is around 12 % larger than the B genome of M. balbisiana, with small intraspecific variation in nuclear DNA found in a number of wild acuminata diploid and parthenocarpic bananas, whereas large variation seems to be exhibited among triploid varieties [102,99].…”
Section: Flow Cytometrymentioning
confidence: 99%